2 answers:
Answer:
6ab + -3a2
Step-by-step explanation:
2ab(4a2 + 3ab - 7b2) original problem
2ab(3ab + 4a2 - 7b2) commutative property
2ab(3ab + -3a2) subtract
4 - 7 = -3
6ab + - 3a2 mulitiply
2ab x 3ab = 6ab
and that is you final expression, you can't add the last 2 numbers cause they are not like terms.
Answer:
1.8ab²
2.7xy⁶
3.7x²
4.8x²+4
5.43y⁵+21
Step-by-step explanation:
yan palang po ung nasagutan ko hindi ko pa po alam kung tama pero yan na ung solution : )
You might be interested in
800|2
800|2
400|2
200|2
100|2
50|2
25|5
5|5
1
Answer:
(2 x 5 x 5) / (2 x 3 x 4 x 5)
=40/120
= 4/12
= 1/3
Answer:
Step-by-step explanation:
i do not know
Answer:
Step-by-step explanation:
2x +2 = 3x - 52
-2x -2x
2 = x -52
+52 +52
50 = x